The effect of calcium oxide from waste chicken eggshell on HZSM-5 - Nor Shamirah, Mohamad Ali; Balasundram, Vekes; Shameli, Kamyar; Norazana, Ibrahim; Ruzinah, Isha; Zainuddin, Abdul Manan (AIDIC Servizi, 2021)
The main objective of the current work is to investigate the influence of waste chicken eggshell (WCE) as an alternative source of calcium oxide (CaO) on Hydrogen exchanged Zeolite Socony Mobil-5 catalyst (HZSM-5). WCE as promoter was loaded at 1wt.% on HZSM-5 catalyst which act as support via incipient wetness impregnation method. The HZSM-5, commercial CaO, and WCE were individually prepared for comparison with WCE/HZSM-5. Synthesized catalysts were characterized via X-Ray Diffraction to analyse the phase purity, Field Emission Scanning Electron Microscopy to analyse the surface morphology, and Brunauer-Emmett-Teller to analyse the surface area and pore size. The addition of WCE on HZSM-5 has significantly affected the framework structure of HZSM-5 where the crystallinity percentage and average crystal size of HZSM-5 drastically dropped to 44.97 % and 45.00 nm. The original cubic-like structure in HZSM-5 has significantly altered into a netlike structure after the impregnation of WCE. A similar effect of alteration was observed on BET surface area dropped from 365.81 m2/g (HZSM-5) to 292.14 m2/g (WCE/HZSM-5). Interestingly, the pore diameter of WCE/HZSM-5, WCE, and HZSM-5 catalysts was similar at 3.88 nm, 3.87 nm, and 3.87 nm respectively. WCE and commercial CaO almost share similar textural properties. Hence, the addition of WCE as an alternative source of calcium oxide into HZSM-5 can provide a high catalytic reaction and stable surface in catalytic cracking of heavy hydrocarbons into small hydrocarbons with longer catalyst lifetimes.